Predicting the stress-strain behavior of mine tailing using modified hyperbolic model - Adajar, Mary Ann Q. (Animo Repository, 2016)
The shear strength behavior of mine tailings was investigated through direct shear test to determine its applicability as embankment material. Dry tailings at very dense initial state and lower normal stresses exhibited peak shear strength and strain softening with dilative behavior, indicating that tailing samples failed in brittle manner. At higher normal stresses, the dry tailing samples attained the critical state shear stress and the volumetric strain is purely compressive. Tailings in dry condition manifested a strong particle interlock as indicated by high critical state friction angle ranging from 36.6° to 38.4°. Peak shear stress was not observed for saturated tailings even at very dense condition and low normal stresses indicating that saturated tailings have ductile behavior with contractive volumetric strain. Friction angles at failure of saturated tailings were lower at an average of 4o as compared to those obtained in dry condition. Modified hyperbolic model was formulated to predict the shear stress against shear strain and volumetric strain against shear strain responses of tailings to different stresses. The modified hyperbolic model provides a good approximation to the stress-strain and volumetric strain-shear strain responses measured during the tests of tailings that exhibited a ductile failure and compressive volumetric strain. However, the model does not give a good prediction of stress-strain response for specimens that exhibited brittle failure with dilative volumetric strain. The model cannot capture the strain softening phenomena, but it can be used to model the behavior leading to the strain softening as well as during the ductile stage.